WANA KERTIH: Konsep Penyucian Dan Pelestarian Hutan Masyarakat Hindu Bali - I Gede Sutana; Gede Yoga Satrya Wibawa; Ni Putu Evi Setiawati (Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja, 2021)
Forests are sources of life that provide oxygen and sources of food for the survival of species on earth. The existence of forests is now increasingly worrying with the existence of deforestation and forest and land fires which cause damage to the forest. Various efforts have been made by the government, particularly the Indonesian government, to undertake ecological disasters related to forests. In the life of the Balinese Hindu community, there is a concept of forest preservation and protection known as the concept of Wana Kertih which is part of Sad Kertih. In the context of the relationship between the Balinese Hindu community and the forest, the Balinese Hindu people respect and purify the mountains and forests as the highest respect for Lord Shiva. In Bali, the forest, apart from having a general function as is well known, also has social, religious and cultural functions because forests are highly correlated with the religious ritual life of Balinese Hindus under the auspices of the Traditional Village. In the concept of Wana Kertih, there are three functions of forests to develop sustainable forests (wana asri), including: (1) maha wana (forest as a source of life); (2) tapa wana (forest as a spiritual means); (3) sri wana (forest as a means / source of the community's economy). The concept of Wana Kertih is arguably entrenched in the life of the Balinese Hindu community. This is evidenced by the implementation of the Wana Kertih concept in life of the Balinese Hindu community. Some forms of implementation of the Wana Kertih concept in life of the Balinese Hindu community include: (1) the existence of Tumpek Wariga / Tumpek Uduh; (2) the existence of the Alas Angker Temple; (3) the existence of large trees using saput poleng; and (4) there are regulations or awig-awig related to forest preservation and protection.